Green Tea and Rosemary Extracts in Free and Encapsulated Liposome Forms: Natural Antioxidants in Sports Science - Jahanfar, Shima; Khosravi-Darani, Kianoush; Jahadi, Mahshid; Mousavai Khanghah, Amin (International Journal of Sport Studies for Health, 2025)
Natural Antioxidants are compounds with many advantages, but their applications have some limitations, including bioavailability and instability. Liposomes are appropriate carriers that can be used for antioxidants to protect them from unfavorable conditions. Therefore, they are used in various cosmetic, pharmaceutical and food industries. One of the most critical applications of liposome antioxidants in medicine is cancer prevention, which happens by reducing oxidative stress. Encapsulated liposome antioxidants increase the therapeutic effects because the higher drug concentrations reach the cancer tissue. Also, due to the harmful effects of synthetic antioxidants, the use of natural antioxidants has increased. Polyphenols have strong antioxidant properties. This study critically reviews the green tea and rosemary extracts as natural antioxidants and their encapsulation. Green tea and rosemary extracts indicated excellent antioxidant properties in food oils. Also, the encapsulated green tea and rosemary extracts in liposomes had more substantial antioxidant features than their free forms. Green tea extracts in both free and encapsulated liposomes had strong antioxidant properties in canola oil, while liposomes containing green tea extracts acted better than free forms of extracts and synthetic antioxidants and caused the production of the first and second products to be delayed. Some of the natural antioxidants have more potent antioxidant properties than synthetic antioxidants, such as BHT, which causes the oxidation ratio in food oils to be delayed. The controlled release and the better performance of natural antioxidants cause the encapsulation of polyphenols.